UPAYA MENINGKATKAN KETERAMPILAN MENULIS SLOGAN/POSTER DENGAN MEDIA GAMBAR PADA SISWA TUNARUNGU KELAS VIII SMPLB DI SLB SUHARJO PUTRA PATUK GUNUNGKIDUL - Isah Rahmawati; Wijaya Heru Santosa (Universitas Sarjanawiyata Tamansiswa, 2015)
Research aims were 1) describing the learning process of Indonesian language using picture media in order to improve skill of writing slogan or poster; 2) describing the improve of learning result after the using picture media in writing lesson of slogan or poster. Research method: this research was done in two cyclus, cyclus I and cyclus II. Data was retrieved from observation, test, field, and documentation. Results: The result shown1) In the cyclus I, the writing lesson of slogan or poster by using picture media makes the student become active to follow and focus than before. In the cyclus II, the ability of the student to write slogan or poster look improve than before. 2) The scoring analysis shown that the skill of write slogan or poster of the student improve 67,21 score compare with pra cyclus. In the cyclus I has 78,33 score and in the cyclus 2 improve become 92,77. In the cyslus I, the aspect of properly content of slogan or poster with theme has 9.3 score; the aspect of use short, clear, effective and full of meaning the language has 7,67 score; the aspect of properly word and the variation has 6.67 score; the aspect of persuasive slogan or poster has 7.67 score; the aspect of slogan or poster with good creativity and attractive content has score 7.34; the aspect of sentence arrangement of poster or slogan and idea improvement has 8.33 score.In the cyslus II, the aspect of properly content of slogan or poster with theme has 9.67 score; the aspect of use short, clear, effective and full of meaning the language have 8.33 score; the aspect of properly word and the variation had 8.66 score; the aspect of persuasive slogan or poster had 10 score; the aspect of slogan or poster with good creativity and attractive content had score 9; the aspect of sentence arrangement of poster or slogan and idea improvement has 10 score.Research aims were 1) describing the learning process of Indonesian language using picture medias in order to improving skill of writing slogan or poster; 2) describing the improve of learning result after the using picture media in writing lesson of slogan or poster. Research method: this research done in two cyclus, cyclus I and cyclus II. Data was retrieved by observasion, test, field and documentation.Results: The result shown1) In the cyclus I, the writing lesson of slogan or poster by using picture media makes student become active to follow and focus than before. In the cyclus II, the ability of the student to write slogan or poster look improve than before. 2) The scoring analysis shown that that the skill of write slogan or posterÂ of the student improve 67,21 score compare with pra cyclus. In the cyclus I has 78,33 scoreÂ and in the cyclus 2 improve become 92,77. In the cyslus I, the aspect of properly content of slogan or poster with theme has 9.3 score; the aspect of use short, clear, efective and full of meaning the language has 7,67 score; the aspect of properly word and the variation has 6.67 score; the aspect of persuasif slogan or poster has 7.67 score; the aspect of slogan or poster with good creativity and atractive content has score 7.34; the aspect of sentense arrangement of poster or slogan and idea improvement has 8.33 score.In the cyslus II, the aspect of properly content of slogan or poster with theme has 9.67 score; the aspect of use short, clear, efective and full of meaning the language have 8.33 score; the aspect of properly word and the variation had 8.66 score; the aspect of persuasif slogan or poster had 10 score; the aspect of slogan or poster with good creativity and attractive content had score 9; the aspect of sentense arrangement of poster or slogan and idea improvement has 10 score.